Genomic characterization of antimicrobial-resistant Salmonella enterica in chicken meat from wet markets in Metro Manila, Philippines - Nagpala, Michael Joseph M.; Mora, Jonah Feliza B.; Pavon, Rance Derrick N.; Rivera, Windell L. (Frontiers in Microbiology, 2025)
The emergence of multidrug-resistant (MDR) Salmonella is recognized as a significant public health problem worldwide. This study investigated the occurrence of MDR Salmonella serovars in chicken meat from wet markets in Metro Manila, Philippines from February to July 2022. Using whole genome sequencing (WGS) and phenotypic antimicrobial resistance (AMR) testing, the serovar, drug resistance, and virulence profiles of Salmonella isolates were characterized. Out of 253 chicken cut samples, 95 S. enterica isolates representing 15 distinct serovars were recovered. The most common was S. enterica serovar Infantis (51.58%), followed by S. Brancaster (9.47%), S. Anatum (7.37%), S. London (7.37%), S. Uganda (6.32%), and S. Derby (4.21%). Phenotypic AMR testing revealed that 73.68% of the isolates were resistant to at least one drug class, and 45.26% were MDR. A wide array of antimicrobial resistance genes (ARGs) associated with resistance to 12 different drug classes was identified, including three β-lactamase gene variants: blaCTX-M-65, blaTEM-1, and blaTEM-176. Some of these ARGs were located on MDR plasmids, such as those on IncFIB(K)_1_Kpn3, IncFIA(HI1)_1_HI1, and IncX1_1. A total of 131 virulence genes were detected, some of which conferred pESI-like characteristics to S. Infantis. These findings highlight a potential public health risk posed by pathogenic MDR Salmonella in chicken meat and underscore the urgent need for further research and coordinated AMR surveillance in the Philippines, aiming to stimulate national efforts to combat AMR.